Employer Branding, Job Burnout: Do They Effect on Employee Engagement in Certain Educational Foundation Sector in Indonesia? - Fauziah Adinda Kusuma; Anita Silvianita (Journal of International Conference Proceedings, 2023)
Employer branding design is important to create a good corporate image for both internal and external companies. Many studies have said that employer branding affects employee engagement because a good company image can make employee engagement and dedication increase to their work. In the XYZ foundation in Indonesia, there was a 1,49% decrease in the value of their Employee Engagement Index (EEI). The decline in the EEI at the XYZ foundation is assumed to be due to the absence of employer branding design at the foundation, and mediated or added by a fairly high employee burnout rate of 16.28%. The purpose of this study is to determine and analyze the influence or the importance of employer branding on employee engagement through job burnout as an intervening variable that mediates it. The method used in this study is quantitative with the technique of distributing questionnaires to foundation employees, then the results will be calculated using SMART PLS ver. 3.9 accompanied by descriptive analysis for explanation.Keywords: Employer branding, job burnout, employee engagement